1998
DOI: 10.1002/(sici)1097-0142(19980101)82:1<42::aid-cncr5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cachexia due to cancer on whole body and skeletal muscle protein turnover

Abstract: Conflicting data in the literature may be accounted for by the different selection of patients and controls. Furthermore, WBP kinetics is the result of the metabolism of at least two compartments, the muscle and the nonmuscle compartments (including the tumor), which can change in opposite ways. In patients with cachexia due to cancer, the skeletal compartment appears to be the more compromised, with a significant decrease in SMP synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 33 publications
1
28
0
2
Order By: Relevance
“…Additionally, documentation of increased urinary excretion of nitrogen in dogs with OSA reflected increased protein turnover and greater protein catabolism in those dogs, compared with control dogs. Our results are similar to those of others 1,9,31,55 who have documented increased protein catabolism in humans with neoplasia. Urinary nitrogen excretion for dogs with OSA in the study reported here was quantitatively similar to that reported for other dogs requiring intensive care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, documentation of increased urinary excretion of nitrogen in dogs with OSA reflected increased protein turnover and greater protein catabolism in those dogs, compared with control dogs. Our results are similar to those of others 1,9,31,55 who have documented increased protein catabolism in humans with neoplasia. Urinary nitrogen excretion for dogs with OSA in the study reported here was quantitatively similar to that reported for other dogs requiring intensive care.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3][4][5][6][7][8][9][10][11] Indirect calorimetry has become standard for use in human and veterinary research to determine REE and metabolic energy requirements (MER). [12][13][14][15][16] Metabolic energy requirements for healthy dogs have been known for many years [17][18][19] ; however, MER have only recently been determined directly from animals with neoplasia.…”
mentioning
confidence: 99%
“…In patients with advanced gastric cancer, an increase in skeletal muscle protein breakdown was shown without a significant change in total body protein turnover [20]. Some of the other reported abnormalities include increased resting energy consumption, impaired muscle protein synthesis, abnormalities in adenosine triphosphate (ATP) generation, and intracellular calcium flux.…”
Section: Neuromuscular Abnormalitiesmentioning
confidence: 99%
“…Although some of these mechanisms still remain to be fully elucidated, skeletal muscle wasting clearly occurs because of perturbations in muscle protein metabolism, including decreased muscle protein synthesis, increased muscle protein degradation, or a combination of both (see Figure 1). Such perturbations have been documented in tumor-bearing animals (Emery, Lovell, & Rennie, 1984;Pain, Randall, & Garlick, 1984;Samuels et al, 2001) and in weight-losing cancer patients (Drowzak, Ferrari, Gavazzi, Maiorana, & Bozzetti, 1998;Emery, Edwards, Rennie, Souhami, & Halliday, 1984;Lundholm, Bylund, Holm, & Schersten, 1976;Lundholm et al, 1982).…”
Section: Mechanisms Underlying Cancer-related Skeletal Muscle Wastingmentioning
confidence: 92%